2013
DOI: 10.1530/joe-12-0339
|View full text |Cite
|
Sign up to set email alerts
|

A role of prostaglandin transporter in regulating PGE2 release from human bronchial epithelial BEAS-2B cells in response to LPS

Abstract: Naturally occurring prostaglandin E 2 (PGE 2 ) plays a role in inflammatory responses through eicosanoid signaling pathways. PGE 2 is impermeable to cell membranes at physiological pH and needs solute carrier across the membranes; however, it remains unclear how intercellular concentrations of PGE 2 are regulated under the condition of inflammation. We aimed to clarify a role of organic anion-transporting polypeptide 2A1 (OATP2A1/SLCO2A1), also known as prostaglandin transporter (PGT), in PGE 2 release from ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Odontoblasts with Pgt and Ep2 immunoreactivity throughout their cytoplasm, including in the cellular processes, lost their immunoreactivity after pulpotomy; newly differentiated odontoblast-like cells acquired Pgt and Ep2 immunoreactivity in their cellular processes. Previous in vitro studies demonstrated that MTA significantly increased PGE 2 production in dental pulp cells in a time-dependent manner 6 and that Pgt was involved in the efflux of intracellularly produced PGE 2 into the extracellular milieu 23 . Taken together, these findings indicate that PGE 2 released by Pgt stimulates odontoblast differentiation during MTA-induced pulpal wound healing in an autocrine/paracrine manner by binding to Ep2/Ep4.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Odontoblasts with Pgt and Ep2 immunoreactivity throughout their cytoplasm, including in the cellular processes, lost their immunoreactivity after pulpotomy; newly differentiated odontoblast-like cells acquired Pgt and Ep2 immunoreactivity in their cellular processes. Previous in vitro studies demonstrated that MTA significantly increased PGE 2 production in dental pulp cells in a time-dependent manner 6 and that Pgt was involved in the efflux of intracellularly produced PGE 2 into the extracellular milieu 23 . Taken together, these findings indicate that PGE 2 released by Pgt stimulates odontoblast differentiation during MTA-induced pulpal wound healing in an autocrine/paracrine manner by binding to Ep2/Ep4.…”
Section: Discussionmentioning
confidence: 98%
“…Carrier-mediated transport appears to compensate for its limited passive diffusion 20 22 . Prostaglandin transporter (Pgt) is one of the most studied transporters involved in the cellular release of PGE 2 23 . We have previously reported that endothelial cells in rat incisor pulp tissue are associated with the biosynthesis of PGE 2 , and that multidrug resistance-associated protein-4 and Pgt contribute to the transport of PGE 2 in the transmembrane pathway 20 .…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the fact that lipid mediators do not rely on vesicular traffic to be secreted, compartmentalized synthesis depends on the translocation and assembly of specific enzymatic complexes necessary for the synthesis of a particular mediator [65]. Moreover, the release of the negatively charged lipid mediators to the extracellular environment relies on organic anion transporters of the ATP-binding cassette type III family, known as MRPs (multidrug-resistant related proteins) and SLCs (soluble carrier super family) [6669]. This dependence on a membrane localized anionic transporter may account for differences in the release of specific mediators.…”
Section: Discussionmentioning
confidence: 99%
“…100,101 Recent genome-wide association studies indicate a link of loss-of-function mutations in SLCO2A1 with primary hypertrophic osteoarthropathy 102 and chronic non-specific multiple ulcers of the small intestine. 103 Because PGE 2 is anti-fibrotic to lung stromal cells 104 and OATP2A1 is expressed functionally in mouse lungs 105 and the human bronchial epithelial BEAS-2B cells, 106 the effect of the absence of Slco2a1 on pulmonary fibrosis in intra-tracheally bleomycininjected mice was studied. 107 Immunohistochemistry showed that abundant expression of Oatp2a1 in mouse type 1 alveolar epithelial cells (AT1) and PGE 2 uptake was almost diminished in Figure 2.…”
Section: Pathophysiological Role Of Prostaglandin Transporter Oatp2a1mentioning
confidence: 99%